2017
DOI: 10.1073/pnas.1614837114
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of expression-state boundaries by Rif1 and Taz1 in fission yeast

Abstract: The Shelterin component Rif1 has emerged as a global regulator of the replication-timing program in all eukaryotes examined to date, possibly by modulating the 3D-organization of the genome. In fission yeast a second Shelterin component, Taz1, might share similar functions. Here, we identified unexpected properties for Rif1 and Taz1 by conducting high-throughput genetic screens designed to identify cis-and transacting factors capable of creating heterochromatin-euchromatin boundaries in fission yeast. The prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Recent studies showed that it also plays important roles in DNA damage response and DNA replication timing ( 18 , 27 , 31 , 35 , 36 , 56 ). However, Rif1 has long been implicated in heterochromatin regulation in both yeast and mammalian cells ( 37 , 66 68 ), suggesting that it may have other conserved functions. Indeed, the Rif1 homologue from drosophila does not fully complement yeast or mammalian Rif1 function in DNA damage response ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that it also plays important roles in DNA damage response and DNA replication timing ( 18 , 27 , 31 , 35 , 36 , 56 ). However, Rif1 has long been implicated in heterochromatin regulation in both yeast and mammalian cells ( 37 , 66 68 ), suggesting that it may have other conserved functions. Indeed, the Rif1 homologue from drosophila does not fully complement yeast or mammalian Rif1 function in DNA damage response ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…The new screens reported here build on our recent identification of DNA elements capable of functionally replacing the natural chromatin boundary, IR-R + , at the edge of the mating-type region ( Jakociunas et al 2013 ; Toteva et al 2017 ). IR-R + deletion leads to reduced heterochromatic silencing ( Thon et al 2002 ) that can be restored by artificial boundaries.…”
mentioning
confidence: 99%
“…Another surprising finding of this work is the identification of RIF1 as a positive regulator of Xist expression. Although we have previously shown that RIF1 is associated with a number of GC-rich TSSs in mESCs 45 , most of the evidence linking RIF1 to gene expression suggests its function as a negative regulator [48][49][50][51][52] . In general, RIF1 is associated with silenced chromatin regions, raising the question of what the molecular mechanism of this positive control could be.…”
Section: Discussionmentioning
confidence: 88%
“…RIF1 is a multifaceted protein, required for the regulation of several of the nuclear processes that take place during XCI. RIF1 is the only known genome-wide regulator of replication timing [40][41][42][43][44][45][46] , it confines long-range chromatin contacts within the respective boundaries of the nuclear A/B compartments 47 and plays an as yet unclear function in the control of gene expression 45,[48][49][50][51][52] . RIF1 is an adaptor for Protein Phosphatase 1 (PP1), one of the main Ser/Thr phosphatases in eukaryotic cells 42,[53][54][55][56][57][58] .…”
Section: Introductionmentioning
confidence: 99%